2009
DOI: 10.5694/j.1326-5377.2009.tb02910.x
|View full text |Cite
|
Sign up to set email alerts
|

Does point‐of‐care testing lead to the same or better adherence to medication? A randomised controlled trial: the PoCT in General Practice Trial

Abstract: Objective: To compare the clinical effectiveness of point‐of‐care testing (PoCT) with that of pathology laboratory testing, as measured by patients’ adherence to medication. Design: Multicentre, cluster randomised controlled trial using non‐inferiority analysis. Medication adherence was assessed twice (in April 2006 and January 2007) by a self‐administered questionnaire using the five‐item Medication Adherence Report Scale (MARS‐5). Setting: 53 Australian general practices in urban, rural and remote areas acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 24 publications
1
57
0
2
Order By: Relevance
“…Twenty-three of the studies used a control group for comparisons [15,17–20,22–28,3040]. All of the studies focused on adults with T2DM [15–41], but one study also included individuals diagnosed with Type 1 diabetes [24]. Thirteen of the 27 articles were conducted in international locations [15,22–24,2831,3435,37–38,41].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-three of the studies used a control group for comparisons [15,17–20,22–28,3040]. All of the studies focused on adults with T2DM [15–41], but one study also included individuals diagnosed with Type 1 diabetes [24]. Thirteen of the 27 articles were conducted in international locations [15,22–24,2831,3435,37–38,41].…”
Section: Resultsmentioning
confidence: 99%
“…All forms of indirect methods were used, with 18 studies measuring medication adherence by self-report [15–17,21,2332,35,37,3941], two by pill count [22,33], three by electronic devices [1819,38], and three by pharmacy claims data [20,34,36]. Of the 27 studies, 13 reported statistically significant differences in medication adherence in the intervention group compared with the control group [15,17–20,22,24,28,3031,33,36,40]. All four studies without a control group reported statistically significant changes in medication adherence [16,21,29,41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicians’ uptake of validated best care procedures remains stubbornly around 50% or less for most advances in therapeutics [1],[2]. Combined with a similar rate of patient adherence with self-administered treatments [3], the average effectiveness of therapies reaches typically only about a quarter (50% - 50%) of their potential.…”
Section: Introductionmentioning
confidence: 99%